[OP.7A.06] FIRST-IN-HUMAN EVALUATION OF A TRANSVENOUS CAROTID BODY ABLATION DEVICE TO TREAT PATIENTS WITH RESISTANT HYPERTENSION. (September 2017) - Schlaich, M.; Sievert, H.; Reddy, V.; Hering, D.; Schultz, C.; Shetty, S.; Worthley, S.; Malek, F.; Kmonicek, P.; Neuzil, P.
Abstract : Objective: The carotid body (CB), a chemoreceptor located at the carotid bifurcation, is considered a therapeutic target in diseases mediated by the sympathetic nervous system. The objective of this study was to establish the safety and to assess the effectiveness of a catheter-based system to ablate the carotid body and reduce blood pressure (BP) in patients with resistant hypertension. Design and method: This single-arm multicenter prospective study was approved for treatment of 30 patients. Inclusion criteria included stable prescriptions of three or more antihypertensive medications for at least six weeks prior to the procedure, office systolic BP above 160mmHg, confirmed presence of the right CB by CT angiography, and confirmation of resistant hypertension with daytime systolic ambulatory BP above 135mmHg on two consecutive occasions during screening period. The primary safety endpoint was the combined rate of death, hospitalization for hypertensive crisis, and device- or procedure-related serious adverse event (SAE) at one month post-treatment. Effectiveness was defined as the change in 24-hr systolic ambulatory BP between baseline and 1, 3, and 6 months post-treatment. The carotid body ablation was performed using aproprietary ablation catheter system (Cibiem, Inc.) delivering ultrasound energy via the jugular vein under intravascular imaging guidance. Results: To date, preliminary data is available on 15 hypertensive patients with a mean age of 66Y[REPLACEMENT CHARACTER]Y10 years, 58% male, mean BMI of 30.2Y[REPLACEMENT CHARACTER]Y4.3Ykg/m 2, and diabetes in 40%. Mean baseline 24-hr ABPM was 152Y[REPLACEMENT CHARACTER]Y11Y/ 89Y[REPLACEMENT CHARACTER]Y12YmmHg. At one month, two SAEs had been reported (one transient ischemic attack and one hospitalization for hypertensive crisis). 24-hr ABPM was reduced by an average of 9Y[REPLACEMENT CHARACTER]Y9/4Y[REPLACEMENT CHARACTER]Y6YmmHg. At 6months no further SAEs had been reported and ABPM showed reduction of 7Y[REPLACEMENT CHARACTER]Y19/5Y[REPLACEMENT CHARACTER]Y7YmmHg compared to baseline. Conclusions: Transvenous catheter based ablation of the carotid body appears to be a safe approach with promising results in the treatment of patients with resistant hypertension that need to be confirmed in future larger randomized evaluations. A complete follow-up dataset will be available for presentation at the time of the meeting.